ESG Practices and Islamic Finance Principles During Geopolitical Uncertainty: A Methodologically Rigorous Test on Indonesian Capital Markets (2011–2024) - Alwahidin La Pade; Amanda La Hadi; Alija Avdukic; Mohammad Nur Rianto Al Arif (Journal of Islamic Monetary Economics and Finance, 2026)
This study examines whether ESG and Shariah compliance has synergistic crisis buffers for Indonesian capital markets based on the stakeholder theory and Islamic finance stability principles. Using 3,976 firm-year observations (2011-2024) and System-GMM estimation, we find no significant interaction effects of ESG and Shariah during geopolitical crises. However, we identify four boundary conditions for the null findings: (1) market saturation (73.9% Shariah compliance erodes firm differentiation); (2) crisis specificity (systemic shocks transcend firm-level stakeholder adaptations); (3) parallel legitimacy (ESG and Shariah accommodate distinct stakeholder channels); and (4) measurement horizon (short-term returns overlook stakeholders' long-term value). Theoretically, we establish that stakeholder benefits depend on firm differentiation, and crisis type specificity—applicable to idiosyncratic, but not systemic crises. Practically, regulators should treat sustainable finance and Islamic finance as dual development pathways, and investors should use an ESG-Shariah framework to foster non-financial well-being during a crisis, not to seek return generation. Our contributions not only offer empirical boundary conditions for stakeholder theory in developing Islamic markets but also demonstrate how methodological factors influence values-based investing studies. The findings are contingent on our governance-centric ESG proxy, the elevated Shariah compliance percentage in Indonesian markets, and the short-term return-focused evaluation outcome. Acknowledgment This research is supported by the BIB-LPDP scholarship from the Ministry of Religious Affairs (Kementerian Agama), Republic of Indonesia. The authors would like to express their gratitude for the funding and support provided throughout this study.